Effect of Thermal Aging and Chemical Treatment on Tensile Properties of Coir Fiber. Issue 1 (2nd January 2018) - Manjula, R; Raju, NV; Chakradhar, RPS; Johns, Jobish
ABSTRACT: Effect of thermal aging and chemical treatment on the physical properties of coir fiber was investigated. Coir fibers were treated with sodium hydroxide and glutaraldehyde for 2 h. The influence of alkali and aldehyde treatment on tensile strength and elongation at break was studied in detail. Enhancement in tensile strength of coir fiber was observed up to five days of aging at 50°C and further decreased. Thermal cross linking of cellulose present in the fiber may be the reason for the increase in tensile strength and thermal degradation due to the chain scission of cellulose reduced the tensile strength. Sodium-hydroxide-treated samples showed an increase in tensile strength and reduction in elongation at break. The removal of impurities such as waxy and fatty acid residues from the coir fiber by reacting with strong base solution improved the strength of fiber. Cross linking of cellulose with glutaraldehyde in the fiber reduced the elasticity and enhances the strength of the material. Scanning electron microscopy was employed to analyze the change in surface morphology upon chemical treatment. Improvement in the tensile strength suggests that NaOH and glutaraldehyde can be effectively used to modify coir fiber with excellent physical properties.